Deep Femoral Vein Reconstruction of the Abdominal Aorta and Adaptation of the Neo-Aortoiliac System Bypass Technique in an Endovascular Era. (January 2019) - Nordanstig, Joakim; Törngren, Kristina; Smidfelt, Kristian; Roos, Håkan; Langenskiöld, Marcus
Background: Primary infection of the abdominal aorta is a rare pathology that may threaten the integrity of the aortic wall, while secondary aortic prosthesis infection represents a devastating complication to open surgical and endovascular aortic surgery. Curative treatment is achievable by removal of all infected prosthetic material followed by a vascular reconstruction. Design and Methods: Twelve consecutive patients treated with the neo-aortoiliac system bypass (NAIS) procedure were reviewed. Nine were treated for a secondary aortic prosthesis infection (tube graft n = 3, bifurcated graft n = 4, endovascular aortic repair (EVAR) stent graft n = 1, and fenestrated EVAR [FEVAR] stent graft n = 1), while 3 patients underwent NAIS repair due to an emergent primary mycotic aortoiliac aneurysm. Primary Results: Ten of 12 patients survived 30 days. Three patients were operated on acutely, and 9 patients had elective or subacute NAIS surgery. Two of 3 patients operated acutely died within 30 days, whereas no 30-day or 1-year mortality was observed in patients undergoing elective or subacute surgery. The median time from primary reconstruction to the NAIS procedure was 11 months (range: 0-201 months). Stent grafts (n = 5 of 12) were in 4 cases explanted using endovascular balloon clamping. Of the explanted endografts, 2 patients presented with a secondary graft infection after EVAR/FEVAR, while 3 patients had been emergently treated with endovascular cuffs as a "bridge-to-surgery" procedure due to aortoenteric fistula (AEF). Patients who received a "bridge-to-surgery" regimen were treated with the NAIS procedure within 8 weeks (median 27 days, range: 27-60) after receiving emergency stent grafting. Principal Conclusions: Aortic balloon-clamping during explantation of infected aortic prosthetic endografts is feasible and facilitates complete endograft removal. Endovascular bridging procedures could be beneficiary in the treatment of AEF or anastomotic dehiscence due to graft infection, offering a possibility to convert the acute setting to an elective definitive reconstructive procedure with a higher overall success rate.